2015
DOI: 10.1016/j.jmr.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Gradient-echo 3D imaging of Rb polarization in fiber-coupled atomic magnetometer

Abstract: The analogy between atomic and nuclear spins is exploited to implement 3D imaging of polarization inside the cell of an atomic magnetometer. The resolution of 0.8mm×1.2mm×1.4mm has been demonstrated with the gradient-echo imaging method. The imaging can be used in many applications. One such an application is the evaluation of active volume of an atomic magnetometer for sensitivity analysis and optimization. It has been found that imaging resolution is limited due to de-phasing from spin-exchange collisions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A more important effect might be the non-uniformity of the pumping rate and the polarization level near walls. The study conducted in [32] showed that, despite various issues that can cause non-uniformity of the signal across the cell, the product of spin-density and spin-polarization did not vary much to negatively affect the sensitivity. Although electrical heating used in several atomic magnetometer demonstrations [4,5,6] is quite simple and efficient, it introduces some noise and can lead to interruptions in measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A more important effect might be the non-uniformity of the pumping rate and the polarization level near walls. The study conducted in [32] showed that, despite various issues that can cause non-uniformity of the signal across the cell, the product of spin-density and spin-polarization did not vary much to negatively affect the sensitivity. Although electrical heating used in several atomic magnetometer demonstrations [4,5,6] is quite simple and efficient, it introduces some noise and can lead to interruptions in measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The light path for the pump and probe is still contained in the header of the device. If all optical elements are made of fiber, even for the alkali vapor cell, the spatial resolution will be improved, as only the cell limits the resolution 28 . Compared with the SERF AM of 0.16 fT/Hz 1/2 , fiber‐coupled AM utilized the single light path to minimize the cross‐section of the sensor header.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 6 , a threedimensional spin image was measured using OMRI with a spatial resolution of 0.8 mm × 1.2 mm × 1.4 mm. In Refs.…”
Section: Introductionmentioning
confidence: 99%